2022
DOI: 10.1029/2022gl097836
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation‐Moisture Coupling Over Tropical Oceans: Sequential Roles of Shallow, Deep, and Mesoscale Convective Systems

Abstract: Precipitation over tropical oceans rapidly increases when the environmental column saturation fraction (CSF) increases past a critical value of ∼0.7. Past studies suggested that increased stratiform rainfall greatly contributes to the rapid rainfall enhancement. In this study, the sequential roles of non‐deep convection, deep convection, and mesoscale convective system (MCS) in precipitation‐moisture interactions are examined using 19 years of satellite observations. When CSF is below ∼0.5, non‐deep convection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…The rapid pickup in MCS lifetime rainfall with the lower-free-tropospheric specific humidity is similar to the observed rapid increase in tropical oceanic precipitation when the environmental column saturation fraction (CSF) is higher than ∼0.7 (Bretherton et al, 2004), which is closely related to the rapid enhancement of MCS rainfall as the environment is near saturation (X. Chen, Leung, Feng, & Yang, 2022;Schiro et al, 2020;Wolding et al, 2020). The observed nonlinear increase in MCS mean area with lower-free-tropospheric specific humidity is also consistent with the observed nonlinear increase in stratiform rain area with CSF as highlighted in Ahmed and Schumacher (2015).…”
Section: Conclusion and Discussionsupporting
confidence: 59%
“…The rapid pickup in MCS lifetime rainfall with the lower-free-tropospheric specific humidity is similar to the observed rapid increase in tropical oceanic precipitation when the environmental column saturation fraction (CSF) is higher than ∼0.7 (Bretherton et al, 2004), which is closely related to the rapid enhancement of MCS rainfall as the environment is near saturation (X. Chen, Leung, Feng, & Yang, 2022;Schiro et al, 2020;Wolding et al, 2020). The observed nonlinear increase in MCS mean area with lower-free-tropospheric specific humidity is also consistent with the observed nonlinear increase in stratiform rain area with CSF as highlighted in Ahmed and Schumacher (2015).…”
Section: Conclusion and Discussionsupporting
confidence: 59%
“…(2021) and Chen et al. (2022) is used to investigate the precipitating systems over the BoB. In this method, the hourly 0.1° × 0.1° Integrated Multi‐Satellite Retrievals for Global Precipitation Measurement (GPM) mission (IMERG, Huffman et al., 2019, 2020; Tan et al., 2019) Version 6 precipitation data and the half hourly 4‐km global merged geostationary satellite (Janowiak et al., 2017) infrared brightness temperature ( T b ) data from the National Oceanic and Atmospheric Administration (NOAA) and National Centers for Environmental Prediction (NCEP) are used to identify and track the cloud systems, and subsequently divide them into different types.…”
Section: Methodsmentioning
confidence: 95%
“…Hence, the finding in Table 1 highlights the important role of the lower‐free‐tropospheric moisture in the MCS initiation. Higher lower‐free‐tropospheric moisture limits the negative effects of dry‐air entrainment on the plume buoyancy and facilitates the initiation and organization of tropical MCSs (e.g., Chen et al., 2022; Schiro & Neelin, 2019; Wolding et al., 2020).…”
Section: Physical Mechanisms Responsible For the Diurnal Mcs Initiationmentioning
confidence: 99%
“…The unified Noah land surface physics scheme (F. Chen & Dudhia, 2001 ) handles surface process and the Yonsei University (YSU) boundary layer scheme (Hong et al., 2006 ) is employed. No cumulus parameterization is employed because many studies have demonstrated that the 9‐km grid spacing is sufficient to resolve tropical mesoscale convective systems over the region (Chan & Chen, 2022 ; Chan, Zhang, et al., 2020 ; X. Chen, Leung, Feng, & Song, 2021 ; X. Chen, Leung, Feng, Song, & Yang, 2021 ; X. Chen, Pauluis, Leung, & Zhang, 2018 ; X. Chen, Pauluis, & Zhang, 2018 ; X. Chen & Zhang, 2019 ; X. Chen et al., 2020 ; X. Chen et al., 2022 ; S. Wang et al., 2015 ; Ying & Zhang, 2017 , 2018 ; F. Zhang et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%